Analisis Pengaruh Misalignment Terhadap Vibrasi Dan Kinerja Shaft Propeller Pada Kapal Bantu Rumah Sakit (BRS) 2 - Yogi Pratama; Erifive Pranatal (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Vibration due to misalignment of the propeller shaft is detected using the VA-12 Vibration Analyzer sensor which is equipped with a Piezoelectric Accelerometer PV-571. Vibration measurements are carried out in alignment and misalignment conditions. The VA-12 Vibration Analyzer detection tool displays the results of the Vibration signal. Must be protected against the vibrations generated. Vibration signal analysis is done by looking at or observing the signal amplitude and signal frequency with two conditions of alignment and misalignment. The VA-12 Vibration Analyzer is used to analyze vibration signals and then convert them to Fast Fourier Transform (FFT) and Wavelet Transform (WT). In this analysis, a comparison of vibrations is carried out during alignment and misalignment conditions.